General self-efficacy as a moderator between severity of menopausal symptoms and satisfaction with life in menopausal women - Bień, Agnieszka; Niewiadomska, Iwona; Korżyńska-Piętas, Magdalena; Rzońca, Ewa; Zarajczyk, Marta; Pięta, Beata; Jurek, Krzysztof (Frontiers in Public Health, 2024)
The study aimed to determine whether self-efficacy acts as a moderator between the severity of menopausal symptoms and life satisfaction. The research tools were: The Generalized Self-Efficacy Scale (GSES), The Satisfaction with Life Scale (SWLS) The Menopause – Specific Quality of Life (MENQOL), and a standardized questionnaire comprising questions on the participants’ characteristics. 516 women using health care services who had menopausal symptoms took part in the study. Self-efficacy (GSES) (r = −0.176; p < 0.001) and life satisfaction (SWLS) (r = −0.106; p = 0.016) were negatively correlated with the severity of menopausal symptoms (MENQOL). The self-efficacy correlated positively with satisfaction with life (r = 0.278; p < 0.001). A low level of self-efficacy was associated with a significant and negative relationship between the severity of menopausal symptoms and satisfaction with life (p = 0.005), while at a high and moderate level of self-efficacy, the severity of menopausal symptoms was not associated with life satisfaction (p > 0.05). Self-efficacy moderates the relationship between the severity of menopausal symptoms and life satisfaction in menopausal women. The moderating function of self-efficacy is that, at its low level, an increase in the severity of menopausal symptoms reduces life satisfaction, while at medium and high levels, an increase in the severity of menopausal symptoms does not reduce life satisfaction.